Local National Women's Political Caucus Chapter Announces First Annual "RA RA Awards" - Frank, Deirdre (National Women's Political Caucus)
Short summary of Lupe Anguiano's sociopolitical achievements. Announces Anguiano as honoree of RA RA Award.